CONTINUITY OF MIDWIFERY CARE (CONTINUITY OF CARE) FOR MRS. W AGE 35 WITH RUPTURE PERINEUM DEGREE I AT THE INDEPENDENT PRACTICE OF MIDWIFE RONNI SIREGAR SUNGGAL DISTRICT DELI SERDANG REGENCY NORTH SUMATRA YEAR 2025 - Tarigan, Silvina Irawan; Siti Nurmawan Sinaga; Lidya Natalia Sinuhaji; Lidya Triangga Bawamenewa; Uci Ramadhani; Ratni Nst; Maisya Fitri Anungrah, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Midwifery care is a series of activities or interventions provided by midwives to clients who have specific needs or health problems, particularly in maternal and child health (MCH) services and family planning. Midwifery care refers to the implementation of the roles, functions, and responsibilities of midwives in delivering services to clients with obstetric needs or conditions, including pregnancy, childbirth, the postpartum period, newborn care, family planning, as well as women's reproductive health and public health services. The purpose of this study is to describe the implementation of continuity of care midwifery services for a client throughout pregnancy, childbirth, postpartum period, newborn care, and family planning in Mrs. W at PMB Ronni Siregar, through the application of midwifery care management in accordance with midwives' competencies. The population in this midwifery care activity consists of a pregnant woman, Mrs. W, aged 35 years, pregnant 3 para 2 abortus 0 (G3P2A0), starting from 37 weeks and 1 day of gestation.